Dimensionality engineering of hybrid halide perovskite light absorbers - Peng Gao (Nature Portfolio, 2018)
Organic−inorganic metal halide perovskite solar cells possess high efficiency and low processing cost but suffer poor stability. Here Gao et al. review the recent progress on the 2D–3D mixed perovskites and suggest that greatly improved stability can be achieved without compromising the efficiency.